2015
DOI: 10.1038/srep15138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Microbial Internal Storage Turnover on Nitrous Oxide Accumulation During Denitrification

Abstract: Biological wastewater treatment processes under a dynamic regime with respect to carbon substrate can result in microbial storage of internal polymers (e.g., polyhydroxybutyrate (PHB)) and their subsequent utilizations. These storage turnovers play important roles in nitrous oxide (N2O) accumulation during heterotrophic denitrification in biological wastewater treatment. In this work, a mathematical model is developed to evaluate the key role of PHB storage turnovers on N2O accumulation during denitrification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Mathematical modeling has been proven to be a powerful tool for comprehensively understanding complex microbial processes in biological wastewater treatment 19 29 30 31 32 33 34 35 36 . In this work, 1-D and 2-D mathematical modeling were applied to assess the heterotrophic bacterial growth on three types of microbial products (UAP, BAP, and decay released substrate) from anammox bacteria in anammox biofilm, during the biotransformation of nitrogen compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical modeling has been proven to be a powerful tool for comprehensively understanding complex microbial processes in biological wastewater treatment 19 29 30 31 32 33 34 35 36 . In this work, 1-D and 2-D mathematical modeling were applied to assess the heterotrophic bacterial growth on three types of microbial products (UAP, BAP, and decay released substrate) from anammox bacteria in anammox biofilm, during the biotransformation of nitrogen compounds.…”
Section: Resultsmentioning
confidence: 99%
“…This balance can be disturbed via either a decrease in the production rate of electron equivalents or an increase in reducible N oxides. The amount and degradability of intracellular carbon affects the rate of production of electron equivalents. ,, For example, oxidation of intracellular carbon storage compounds (i.e., poly-β-hydroxybutyrate (PHB)) have been shown to influence the rate of electron-equivalent generation and N 2 O accumulation. The consumption of electron equivalents is governed by the type and amount of nitrogen oxide. For example, NO 3 – concentration governs the overall denitrification rate, but NO 2 – and FNA can lower NO 3 – metabolism and increase N 2 O accumulation by inhibiting N 2 O reductase (Nos) in a dose-dependent manner. , An investigation into the interactions between multiple carbon oxidation pathways and nitrite reduction has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Active synthesis of storage polymers suggested that 'Ca. D. occultata' was experiencing electron acceptor starvation at the time of harvesting, consistent with Mn(III) depletion in the bottles (Liu et al, 2015;Guanghuan et al, 2018). Polyphosphate-related proteins, including phosphate transporters, polyphosphate kinase, polyphosphatase and poly-3-hydroxybutyrate synthesis machinery were detected in the proteome (Table S4).…”
Section: Nutrient Storagementioning
confidence: 76%